Decarboxylative Hydroamination of 3-Arylpropiolic Acids with N-Heterocycles under Transition-Metal-Free Conditions - Pan, Xixian; Wan, Xiaolong; Yu, Xin; Zhang, Hui; Xie, Weiqing (Synthesis, 2014)
A decarboxylative hydroamination cascade reaction of 3-arylpropiolic acids with N-heterocycles under transition-metal-free conditions was developed. 3-Arylpropiolic acids were found to react smoothly with a range of N-heterocycles under the effect of t-BuOK to afford N-vinyl heterocycles in moderate to excellent yields. This reaction represents the first decarboxylative hydroamination of 3-arylpropiolic acids without the aid of a transition-metal catalyst.
Keywords: alkynes; decarboxylation; hydroamination; N-vinyl heterocycle; potassium tert-butoxide